Interactive E-Modules Based on Inquiry-Based Learning on Pressure for Junior High School Students - Jihan Fahira Adinda Putri; Habiddin Habiddin (STEM Education International, 2026)
Many teaching materials still emphasise memorisation of concepts rather than actively involving students in the knowledge construction process. Learning approaches aligned with the characteristics of science are still rarely incorporated into teaching materials. Furthermore, students often struggle to understand abstract scientific concepts due to a lack of appropriate visual aids. In line with this, the purpose of this research is to develop an interactive e-module that integrates an inquiry-based learning model on pressure materials that is not only valid but also easy for students to understand. Research and Development (R&D) with a 4D model approach that has been simplified into 3D, namely define, design, and develop, was implemented as a method. Two lecturers and one science teacher, all competent in science, serve as validation subjects in the development of interactive e-module products in this study. Thirty students from class IX at a public junior high school in Malang who have studied pressure material were selected as subjects in the field trial of this research. A literature review and a questionnaire were used to collect data. Quantitative and qualitative analysis was conducted on the collected data. The validation results show an inter-rater agreement rate of 85%, which falls within the almost-perfect and consistent range, indicating uniform assessment and supporting the feasibility of e-modules for science learning. In addition, the e-module readability test scored 87%, placing it in the very good category, indicating that the e-module is easy for students to understand thanks to simple language, clear sentences, an attractive appearance, and content presented in a structured, independently accessible manner. Although it has not been directly implemented to assess concept understanding, this e-module is designed to facilitate learners' active involvement through various inquiry activities aligned with the inquiry-based learning model.